A case of rheumatoid arthritis with valvular and vocal cord involvement - Kumar, Kanishka; Jayaraman, Harini; Bandgar, Pranay (Indian Journal of Case Reports, 2020)
Chronic inflammatory polyarticular joint pain is the most common presenting feature of rheumatoid arthritis (RA). Apart from it, other system involvement symptoms and signs are frequently associated. We are reporting a case of RA that presented as a respiratory case, was diagnosed to have valvular heart disease and was eventually diagnosed as RA with cardiovascular involvement along with the unique and rarely reported laryngeal involvement causing loss of voice temporarily.